Biotechnology Applications in Fish Nutrition - Makbule Baylan; Gamze Mazı; Sedat Gündoğdu (Turkish Journal of Agriculture: Food Science and Technology)
In order to put cultured species on the market with high quality and few casualties, many important studies are carried out. Most of the researches are conducted in the development of feed and feed ingredients 30-60% of the production cost in farming. Therefore, in aquaculture, an interest in alternative feed ingredients is moving at a very fast rate. In this context, the use of enzymes, probiotics and prebiotics in animal feed has steadily increased in recent years with reasons such as effective control of fish diseases and prevention of infection, strengthening the immune system of fish, increase of the digestibility, reduction of the feed cost, reduction of larval-term mortality, provision of increase in growth, live weight gain, and getting rid of the negative effects of stress.